(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article deals with the theoretical issues of travel essays, their formation in the Kyrgyz literature, the impact on their development of famous travel essays of Russian literature. Genre analyzes the achievements and shortcomings of the essays in the Kyrgyz literature, also carried out ideological and thematic analysis of the best samples of essays K. Zhusupova, K. Bobulova. In conclu- sion, it is noted that despite the weak description, superficial narration of events, phenomena, due to insufficient personal creative experience of the 30s of the formation of the genre of essays, these essays have contributed to the formation and development of this genre.